PEMENUHAN HAK DAN AKSESIBILITAS PENYANDANG DISABILITAS KETENAGAKERJAAN, PERSPEKTIF SOUND GOVERNANCE DI KABUPATEN PASURUAN - Ponto, Rian Afrilla; Sakdiyah, Lailatul; Feradiah, Dian; Habibah, Habibah; Lestari, Wahyu Intan (PARADIGMA: Jurnal Ilmu Administrasi, 2023)
This article discusses efforts to fulfill the rights and accessibility of employment for people with disabilities in Pasuruan Regency using the Sound Governance approach. Sound Governance is a collaboration between the government, foreign investment companies (PMA), and the community to create an inclusive and equitable work environment. This study is a descriptive qualitative research. Data were collected through observation, interviews, and data collection. Data was collected through observation, interviews, and literature study. The data collected was thoroughly analysed to identify barriers, challenges and opportunities in fulfilling the rights and access of persons with disabilities to the world of work. The conclusion of this study is that efforts to fulfil the rights and accessibility of employment for people with disabilities in Pasuruan Regency still face several significant barriers and challenges. Although there are laws and local regulations supporting the rights of persons with disabilities, there needs to be greater cooperation between the government, PMA companies, and the community in order to create an inclusive and fair work environment forpersons with disabilities in Pasuruan Regency.Keyword: Accesibility; Disability; Inclusivity; Employment.